Prolonged Intestinal Mucosal Barium Coating due to Ischemic Necrosis - Vincent H. S. Low (Case Reports in Radiology)
A case of a 63-year-old man with small bowel ischemia six weeks after transplantation surgery is presented. Plain abdominal radiograph obtained several days after ingestion of barium shows the sign of prolonged barium coating indicating severe mucosal damage. Abdominal CT scan demonstrates small bowel wall thickening as well as pockets of peritoneal fluid collections. Most critically, CT allows visualization of subtle traces of dense barium within the dependent portions of this fluid indicating bowel perforation.